2015
DOI: 10.1007/s00586-015-3878-1
|View full text |Cite
|
Sign up to set email alerts
|

Medication reconciliation for patients undergoing spinal surgery

Abstract: Medication safety could be significantly improved by implementation of counter-measures specific to the identified risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…This may be because they believe that the BPMDL provides sufficient information to patients, GP, and/or PLTCS for continuing a patient's usual medication, and that it is not their role to prescribe the patient's usual medication at discharge. Kantelhardt et al [28] similarly reported that medications prescribed by surgeons on discharge were primarily related to postoperative care. A study by Murphy et al [29] found that discharge medication errors occurred in 90 % of cases prior to implementation of a MedRec discharge process in a general surgical ward.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This may be because they believe that the BPMDL provides sufficient information to patients, GP, and/or PLTCS for continuing a patient's usual medication, and that it is not their role to prescribe the patient's usual medication at discharge. Kantelhardt et al [28] similarly reported that medications prescribed by surgeons on discharge were primarily related to postoperative care. A study by Murphy et al [29] found that discharge medication errors occurred in 90 % of cases prior to implementation of a MedRec discharge process in a general surgical ward.…”
Section: Discussionmentioning
confidence: 92%
“…Glintborg et al [26] also found that medication information was generally not properly transmitted at discharge. Kantelhardt et al [28] reported that discharge prescriptions by surgeons were predominantly related to postoperative care. And Murphy et al [29] found discharge medication errors for almost every patient discharged from a surgical ward.…”
Section: Discussionmentioning
confidence: 98%